Reappraisal of the clinical role of metronidazole therapy for Clostridioides difficile infection in Taiwan: A multicenter prospective study - Jen-Chieh Lee; Ching-Chi Lee; Chun-Wei Chiu; Pei-Jane Tsai; Po-Ren Hsueh; Yuan-Ti Lee; Yuan-Pin Hung; Wen-Chien Ko (Journal of the Formosan Medical Association, 2022)
Background/Purpose: Although metronidazole is not recommended to treat Clostridioides difficile infection (CDI) in Western countries, it was still to be recommended for the treatment of non-severe CDI among Taiwanese adults in 2020. This controversy in the clinical role of metronidazole therapy for CDI was examined in a prospective clinical study. Methods: The study was conducted from January 2015 to December 2016 in three hospitals in Taiwan. Metronidazole treatment failure (MTF) was defined as the persistence of diarrhea after six days of treatment, medication modification (shifting to oral vancomycin), or death after five days of therapy. Results: Overall, 325 patients receiving metronidazole for CDI were included. The overall MTF rate was 48.6% (158 patients). Leukocyte counts of >15,000 cells/mL in peripheral blood (odd ratio [OR] 1.81; P = 0.04) and congestive heart failure (OR 3.26; P = 0.02) were independently associated with MTF. The MTF rate for patients with leukocyte counts of ≤15,000 cells/mL and no congestive heart failure, leukocyte counts of >15,000 cells/mL and no congestive heart failure, leukocyte counts of ≤15,000 cells/mL and congestive heart failure, and leukocyte counts of >15,000 cells/mL and congestive heart failure were 44.2%, 51.8%, 73.3%, and 66.7%, respectively. Of note, patients who experienced MTF had a higher recurrence rate of CDI than those with metronidazole treatment success (13.9% vs. 6.0%, P = 0.02). Conclusion: For Taiwanese adults with CDI, the failure rate of metronidazole therapy approached 50%, which suggests the reappraisal of the therapeutic role of metronidazole therapy, especially for patients with leukocytosis or underlying congestive heart failure.